1983
DOI: 10.1002/jso.2930230309
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma in a blind eye

Abstract: A 62-year-old man developed a malignant melanoma in his left eye that had been blind due to trauma for 35 years. This case illustrates the difficulties in detection and early diagnosis of occult malignant melanoma of the uveal tract in phthistic globes. The necessity for long-term follow-up of posttraumatic eyes is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several uveal melanomas, [4,5,7] two adenocarcinomas of the retinal pigment epithelium [2,3] and an unspecified sarcoma [6] have been described (Table 1). In two of those cases, enucleation was performed to relieve the pain and an early stage malignant tumor was found,[2,7] leading to a good prognosis.…”
Section: Case Presentationmentioning
confidence: 99%
“…Several uveal melanomas, [4,5,7] two adenocarcinomas of the retinal pigment epithelium [2,3] and an unspecified sarcoma [6] have been described (Table 1). In two of those cases, enucleation was performed to relieve the pain and an early stage malignant tumor was found,[2,7] leading to a good prognosis.…”
Section: Case Presentationmentioning
confidence: 99%
“…[2345] Painful blind eyes may be a harbinger for intraocular malignancy, and many such cases have been described in literature. [67] Our case presented with acute bleed in a pre-existing staphyloma with prolapsed intraocular contents, which had an underlying melanoma. Such a presentation has not been described in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Sarma et al 3 reported a case of malignant melanoma in the left eye of a 62-year-old man who had been blind due to trauma for 35 years. Perry et al 4 reported a case of occult choroidal malignant melanoma in an eye with spontaneous expulsive choroidal haemorrhage and suggested that this association may be more than a chance occurrence, inasmuch as both are associated with necrosis of the posterior ciliary arteries.…”
Section: Commentsmentioning
confidence: 99%